Clinical-Hormonal Characteristics Of Osteoporosis In Patients With Type 2 Diabetes - Maxammatjonova Asalxon Bozorboy qizi (Genius Journals, 2024)
This article provides a complete overview of the clinical characteristics of osteoporosis in patients with type 2 diabetes. Today, we see diabetes in many people. We need to make it even easier to treat, prevent, know the level of the disease, and examine it. Diabetes does not develop in the absence of factors affecting the disease, but the inclination is higher. Complications from diabetes are caused by internal organ failure.
Keywords: Hyperglycemia; glucose; testpaloskasi; hypercortitism